Personalisasi Dan Platform Pengajaran Digital (Blended Learning, Online Learning, Adaptive Learning - Siti Hawa (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2021)
Abstract: Personalize And Digital Teaching Platform (Mixed Learning, Online Learning, Adaptive Learning)Personalization is an essential part of digital learning so as to determine the relationship between personalization and various important elements in digital learning. The purpose of the study was to determine the importance of personalization in digital learning and to determine the relationship between personalization and various important elements in digital learning. The writing method used is a qualitative descriptive method. Data collection techniques are documentation techniques and data processing techniques using qualitative descriptive techniques. The results of the study show that personalization in digital learning is very important because it is a change in teaching methods and methods in accordance with advances in science and technology. Personalization is closely related to an important element in learning, namely the use of the internet as the main medium in the e-learning learning model. The personalization system is carried out to improve the ability or absorption of students in the use of technology. Approaches that can be taken in personalizing digital learning include: Blended learning (a model or strategy which is basically a combination of the advantages of learning that is carried out face-to-face and virtually), Online learning (Online learning is the result of a learning delivered electronically with using computers and computer-based media), Adaptive learning (multi-media learning program that presents learning media with mobile devices and has the ability to adapt to the characteristics of the user's learning style).Abstrak: Personalisasi Dan Platform Pengajaran Digital (Blended Learning, Online Learning, Adaptive Learning)Personalisasi merupakan bagian esensial dalam pembelajaran digital sehingga untuk menentukan keterkaitan antara personalisasi dengan berbagai elemen penting dalam pembelajaran digital. Tujuan penelitian untuk mengetahui pentingnya personalisasi dalam pembelajaran digital dan untuk mengetahui keterkaitan antara personalisasi dengan berbagai elemen penting dalam pembelajaran digital. Metode penulisan yang digunakan adalah metode deskritif kualitatif. Teknik pengumpulan datanya adalah teknik dokumentasi dan teknik pengolahan data menggunakan teknik deskriptif kualitatif. Hasil penelitian menunjukan bahwa personalisasi dalam pembelajaran digital sangat penting karena merupakan suatu perubahan dalam metode dan cara mengajar sesuai dengan kemajuan ilmu pengetahuan dan ilmu teknologi. Personalisasi sangat terkait dengan elemen penting dalam pembelajaran, yaitu pada pemanfaatan internet sebagai media utama dalam model pembelajaran e-learning. Sistem personalisasi dilakukan untuk meningkatkan kemampuan atau daya serap siswa dalam penggunaan teknologi. Pendekatan yang dapat dilakukan dalam personalisasi pembelajaran digital antara lain seperti: Blended learning (Model ataupun srategi yang pada dasarnya merupakan gabungan keunggulan pembelajaran yang dilakukan secara tatap muka dan secara virtual), Online learning (Pembelajaran online merupakan hasil dari suatu pembelajaran yang disampaikan sacara elektronik dengan menggunakan computer dan media berbasis computer), Adaptive learning (program multi media pembelajaran yang menyajikan media pembelajaran dengan perangkat bergerak dan memiliki kemampuan untuk menyesuaikan dengan karakteristik gaya belajar pengguna).